2019
DOI: 10.3390/batteries5030055
|View full text |Cite
|
Sign up to set email alerts
|

A Bilevel Equalizer to Boost the Capacity of Second Life Li Ion Batteries

Abstract: There is a strong interest in second life applications for the growing number of used electric vehicle (EV) batteries, but capacity variations amongst these used cells present a problem. Even when these cells are matched for capacity, some imbalance is bound to remain, and a few lower capacity cells are also likely to develop after the pack begins its second life. Conventional cell voltage equalizers (EQU) do not address this problem, and they only provide a battery discharge capacity that is exactly equal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Thus, the PEQs compensate for SD at the cell level, and the AEQs compensate for CF at the section level. Previous BEQ references, [28][29][30][31][32], described the basic BEQ functionality, but they did not explain how the role of the PEQs is to provide cell-level SD compensation for the cells within a section, and the role of the AEQs is to provide section-level CF compensation, i.e., two types of equalizers for two different problems. As will be explained later, this is done to minimize cost.…”
Section: Bilevel Equalizer Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the PEQs compensate for SD at the cell level, and the AEQs compensate for CF at the section level. Previous BEQ references, [28][29][30][31][32], described the basic BEQ functionality, but they did not explain how the role of the PEQs is to provide cell-level SD compensation for the cells within a section, and the role of the AEQs is to provide section-level CF compensation, i.e., two types of equalizers for two different problems. As will be explained later, this is done to minimize cost.…”
Section: Bilevel Equalizer Operationmentioning
confidence: 99%
“…Figure 4a shows the schematic for one of the AEQ inductive drivers for the BEQ, and Figure 4b shows the IL current and Q1 gate drive voltage waveforms. More detailed descriptions of circuit operation are provided in [28][29][30][31][32], but the basic process to transfer energy from S1 to S4 is described in the following paragraph. The circuit in Figure 4a corresponds to each of the drivers, 1-3, in Figure 3.…”
Section: Bilevel Equalizer Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be shown that this can be done with an automated process using a BEQ, and this should greatly reduce the required expense and effort. However, there now is a more recent HEQ called the bilevel equalizer (BEQ) [9][10][11][12][13][14][15][16][17] that also provides a battery capacity very close to the cell average, and the extra cost appears to be modest. The question is, will the SL capacity increase be enough to justify the extra cost of the BEQ?…”
Section: Introductionmentioning
confidence: 99%
“…As their market continues to grow, batteries are typically replaced when they degrade to about 80% of their original capacity in demanding applications, such as electric vehicles [13,14]. Although unsuitable for them, these batteries are very cost-effective for other applications, and re-use lifetimes in the range of 10 years have been estimated [15].…”
Section: Introductionmentioning
confidence: 99%